Construção de uma cartilha educativa para portadores da doença de parkinson no Hospital Universitário Walter Cantídio. - Silva, Maria José Gomes da (2020)
Parkinson's disease (PD) is a common neurodegenerative disorder in aging, characterized mainly by bradykinesia, muscle stiffness, rest tremor and postural instability (cardinal signs). Living with this disease therefore has limitations. Educational technology is an innovative and effective strategy to involve patients in their treatment, improving the patient's quality of life, promoting disease control and preventing complications. Recognizing the importance of using educational technologies with a focus on promoting self-care, as well as the involvement of family members and caregivers with PD patients, this study aims to present the process of building an educational booklet, from a study group at the Walter Cantídio University Hospital of the Federal University of Ceará. It is a methodological research, exploratory-descriptive and a case study, having in its exploratory phase the observation of the realities that interpose in the object of study. As for its nature, this is an applied research, since it aims to generate knowledge for practical application, aimed at solving a specific problem. As for technical procedures, it is an action-research and experimental, which happens when it is carried out in close association with an action or with the resolution of a collective problem. The educational booklet was prepared by the team of the research and extension group on Parkinson's diseases, the Living with Parkinson Project. The construction of the booklet took place from April 2019 to March 2020 and consisted of the following steps: bibliographic survey; definition of the topics to be addressed; discussion of guidelines and classes with health education experts; preparation of chapters by the multidisciplinary team and, finally, discussion and review of chapters in group. The booklet consists of 12 chapters, which include fall prevention guidelines, nutrition, treatment adherence, physical activity, cognitive training, compensation mechanisms, relevant measures to delay the complications of the disease and to minimize parkinsonian symptoms. An evaluation of the booklet was also carried out with specialists in the following areas: social workers, designers, physical educators, nurses, pharmacists, physiotherapists, doctors, nutritionists, psychologists and advertisers. They evaluated the booklet regarding objectives, content, language, relevance, illustrations, layout, motivation and culture. The target population (15 patients with Parkinson's disease) assessed the objectives, organization, language, appearance and motivation. The educational booklet entitled "living with Parkinson's" was well evaluated among professionals and target audience (patients). The results of this work are expected to contribute to studies aimed at improving the health education process for patients with Parkinson's, seeking to improve the quality of life of these patients. Subsequently, the booklet will be validated from the point of view of content and relevance, to be distributed to patients in a health education program.